Content Of Educational Activities In Children's Choirs - Davron Gayratovich Azimov (Euro Asian Journal Publishing, 2024)
Bringing up the younger generation as mature, spiritually, harmoniously, aesthetically and artistically formed, cultured people is one of the most pressing issues facing educational institutions today. The article discusses the importance of music education in secondary schools, not only in teaching children to sing, but also in developing vocal and choral skills or listening to music. and the idea that the formation of their skills consists in the formation of their ideological, spiritual, aesthetic culture
Keywords: music education; secondary school music lessons